Possibilities of bioregulation therapy in the treatment of patients with chronic tonsillitis - A. Yu. Ovchinnikov; N. A. Miroshnichenko; Yu. O. Nikolaeva (IRBIS LLC, 2024)
Background. There are numerous diagnostic methods and therapy regimens for chronic tonsillitis (CT). Different methods of treatment in certain conditions do not always show high efficiency, so the search for new ways of conservative management of CT is needed, the main task of which is palatine tonsils preservation.Objective: to evaluate the efficacy and tolerability of a multicomponent preparation with low dosage of active substances Lymphomyosot® in adult patients with CT and cervical lymphadenopathy in real clinical practice.Material and methods. A total of 170 male and female patients aged 18-65 years with CT (simple form and 1st degree toxic-allergic form) and cervical lymphadenopathy were included in an observational, open, prospective study. In the main group (n=85), a combined therapy consisting of standard CT therapy (a course of palatine tonsils lavage with 0.9% NaCl solution) with the addition of Lymphomyosot® was administered. In the control group (n=85), topical non-steroidal anti-inflammatory drugs or phytotherapy were used instead of the studied drug. Ultrasound examination of regional cervical lymph nodes with measuring of their diameter (longitudinal, transverse) was chosen as a parameter of objective assessment of patients' condition dynamics. The results of therapy at Visit 1 and Visit 2 (12±2 days after Visit 1) were compared. The effectiveness of treatment regimens was analyzed according to the following parameters: complaints related to CT; oropharyngoscopic data; evaluation of CT indicators by the doctor and the patients; dynamics of cervical regional lymph nodes size; satisfaction of the doctor and the patients with the clinical effect and tolerability of therapy.Results. The dynamic observation showed a significant decrease in the number of complaints and symptoms according to objective examination, oropharyngoscopy, as well as evaluation of symptoms by the doctor and the patients at Visit 2 in both groups (p<0.001). However, in the main group, where Lymphomyosot® was administered in the complex treatment, there was a more significant decrease in cervical lymph nodes size compared to the control group (p<0.01).Conclusion. The study demonstrated that Lymphomyosot® increased the efficacy of complex therapy, reducing cervical lymphoadenopathy and other manifestations of the disease in patients with CT (simple and 1st degree toxic-allergic forms).